Rain fade analysis for practical free space optic link in tropical region - Al-Khateeb, Wajdi Fawzi Mohammed; Islam, Md. Rafiqul; Myat , Tun Oo (2011)
Attenuation due to rainfall can severely degrade the FSO links operating under tropical weather. It restricts the distance of FSO communication systems and limits the availability for line-of-sight terrestrial link. Practical FSO link has been setup, monitored and analyzed. A commercially available FSO system was installed at 800 m length together with rain fall intensity measurement facility at IIUM Kuala Lumpur campus. This paper is focused on the effect of rain on the FSO link. The rain attenuation on link has been synchronized in real time with rain fall intensity meter to enable link measurement. The measured rain intensity data was used to compare with ITU-R rain attenuation prediction model to validate the model. The measured rain attenuation on link was compared with that predicted by ITU-R prediction model recommended for the microwave link